Spectrum analysis of inborn errors of metabolism for expanded newborn screening in Xinjiang, China - Jingying Zhu; Li Han; Pingjingwen Yang; Ziyi Feng; Shuyuan Xue (PeerJ)
To determine the disease spectrum and genetic characteristics of inborn errors of metabolism (IEM) in Xinjiang province in the northwest of China, 41,690 newborn babies were screening by tandem mass spectrometry from November 2018 to December 2021. Of these, 57 newborn babies were referred for genetic analysis by next-generation sequencing, which was validated by Sanger sequencing. A total of 36 newborn babies and one relative were diagnosed with IEM, and the overall positive predictive value was 29.03%. The overall incidence of IEM in Xinjiang was 1:1,158 (36/41,690). The incidence of amino acidemias, organic acidemias, and fatty acid oxidation disorder were 1:1,668 (25/41,690), 1:4,632 (9/41,690), and 1:20,845 (2/41,690), respectively. Phenylketonuria and methylmalonic acidemia were the two most common inborn errors of metabolism (IEM), accounting for 83% (30/36) of all confirmed cases. Some hotspot mutations were observed for several IEMs, including PAH gene c.158G > A (p.Arg53His) and c.688G > A (p.Val230Ile) for hyperphenylalaninemia. Four mutation types of the MMACHC gene (e.g., c.609G > A (p.Trp203Ter), c.567dupT (p.Ile190fs)) and six mutation types of the MMUT gene (e.g., c.729_730insT (p.Asp244fs)) were found for methylmalonic acidemia. We also found 11 mutations in six genes: PCCB, IVD, GCDH, MCCC1, SLC22A5, and ACADS in this region. This study combined tandem mass spectrometry and next-generation sequencing technology for the screening and diagnosis of IEM. The study provides effective clinical guidance, and the data provide a basis for expanding newborn screening, genetic screening, and IEM gene consultation in Xinjiang, China.